2011
DOI: 10.4103/0970-9290.79969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endodontic irrigating solutions on the microhardness and roughness of root canal dentin: An in vitro study

Abstract: Within the limitation of this study, it is concluded that 0.2% chlorhexidine gluconate seems to be an appropriate irrigation solution, because of its harmless effect on the microhardness and surface roughness of root canal dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 0 publications
6
30
1
3
Order By: Relevance
“…However, these results are in contrast to those of other studies 1,12,20 , most likely due to the standardization of the initial polishing used here; this procedure was not reported in the other studies. Initial roughness standardization is recommended in studies of chemical conditioning because it offers a controlled reference point for the correct and unambiguous assessment of the morphological effects induced by subsequent chemical treatments 9 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, these results are in contrast to those of other studies 1,12,20 , most likely due to the standardization of the initial polishing used here; this procedure was not reported in the other studies. Initial roughness standardization is recommended in studies of chemical conditioning because it offers a controlled reference point for the correct and unambiguous assessment of the morphological effects induced by subsequent chemical treatments 9 .…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that NaOCl is able to significantly decrease the dentin microhardness, even when used alone (G3), which agrees with previous research [810]. When used in the final rinsing for only 3 minutes, this solution does not significantly change the microhardness compared with the values in the groups that did not have a final flush with NaOCl, confirming that its effect is time dependent [8].…”
Section: Discussionsupporting
confidence: 89%
“…These changes can also affect the sealing ability and adhesion of root canal sealers [6, 7]. Studies indicated that sodium hypochlorite (NaOCl), the most commonly used irrigating agent, decreases the microhardness of dentin at all concentrations [810]. With regard to chelating agents, the decalcification effects depend heavily on the irrigant used, the application time, and the solution pH and concentration [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Although CHX was used as a final irrigant in G6 (NaOCl + EDTA + CHX), G7 (NaOCl + PAA + CHX) and G8 (NaOCl + HEDP + CHX), the comparison with the counterpart other groups without the use of CHX solution (G3, G4 and G5) allows the conclusion that this irrigant does not alter the surface roughness as has been shown previously (Ari et al . , Patil & Uppin ).…”
Section: Discussionmentioning
confidence: 99%